"Flora assessment and carbohydrate analysis on nectar of mangrove species in three selected barangays of Matarinao Bay, Philippines. ". - Regorosa, Nicole C.; Gerona, Maria Elisa B. (Nicole C. Regorosa, 2018)
Mangroves are trees, shrubs, palms, or ground ferns that are salt tolerant, which commonly inhabit tropical and subtropical intertidal areas of the world. These provide suitable and safe habitat for bees as they can produce nectar, and provide protection against storm. Matarinao Bay is surrounded by vast areas of mangroves, which are important in trapping sediments from agricultural land; however, carbohydrate analysis on these mangroves for apiculture purposes has not been done yet. This study assessed selected mangrove areas in Matarinao Bay using transect plot method. Also, the carbohydrate present in nectars of mangrove flowers were determined using phenolsulfuric acid assay, as it is essential in assessing the capacity to hold apiculture in mangrove areas. There were 13 species of magroves assessed in three selected mangrove areas in Matarinao Bay, where mangrove area in Brgy. Buenavista, Quinapondan, Eastern Samar was the most diverse and has Sonneratia alba and Rhizophora apiculata as the two most predominant species with an IVI values of 112.05 and 98.86, respectively. Sonneratia alba has 29.01 mg/mL of total carbohydrate content, whereas Rhizophora apiculata has 4.18 mg/mL. These species occur in abundance and, collectively, may be able to suffice the minimum carbohydrate requirement for honeybees.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.